Effects of Maternal Inflammation and Exposure to Cigarette Smoke on Birth Weight and Delivery of Preterm Babies in a Cohort of Indigenous Australian Women - Pringle, Kirsty G.; Rae, Kym; Weatherall, Loretta; Hall, Sharron; Burns, Christine; Smith, Roger; Lumbers, Eugenie R.; Blackwell, C. Caroline (Frontiers in Immunology, 2015)
Sudden Infant Death Syndrome (SIDS), neonatal deaths and deaths from infection are higher among Indigenous Australians. This study aimed to determine the effects of inflammatory responses and exposure to cigarette smoke, two important factors associated with sudden death in infancy, on preterm birth and birth weight in a cohort of Indigenous mothers. Indigenous Australian women (n=131) were recruited as part of a longitudinal study while attending antenatal care clinics during pregnancy; blood samples were collected up to 3 times in pregnancy. Serum cotinine, indicating exposure to smoke, was detected in 50.4% of mothers. Compared with non-Indigenous women, the cohort had 10 times the prevalence of antibodies to Helicobacter pylori (33% v. 3%). Levels of IgG, antibodies to H. pylori and C- reactive protein (CRP) were all inversely correlated with gestational age (P < 0.05). CRP levels were positively associated with maternal body mass index (BMI) (r = 0.449, P = 0.001). The effects of cigarette smoke (cotinine) and inflammation (CRP) were assessed in relation to risk factors for SIDS: gestational age at delivery and birth weight. Serum cotinine levels were negatively associated with birth weight (r = -0.37, P < 0.001), this correlation held true for both male (r = -0.39, P = 0.002) and female (r = -0.30, P = 0.017) infants. Cotinine was negatively associated with gestational age at delivery (r = -0.199, P = 0.023). When assessed by fetal sex this was significant only for males (r = -0.327, P = 0.011). CRP was negatively associated with gestational age at delivery for female infants (r = -0.46, P < 0.001). In contrast maternal BMI was significantly correlated with birth weight. These data highlight the importance of putting programs in place to reduce cigarette smoke exposure in pregnancy and to treat women with chronic infections such as H. pylori to improve pregnancy outcomes and decrease risk factors for sudden death in infancy.